REVITALISASI PROSES PENEGUHAN AKIDAH DALAM MENGHADAPI CABARAN PASCAMODENISME - Stapa, Dato’ Zakaria (UIN Ar-Raniry, 2014)
Pascamodenisme had been actively sneaking in all sectors of life and leads to a change in setting values and lifestyle. As willingly to lerated, if it controlled atmosphere and pulse Western life, it is also certainly appears to be an image and the image is immediately admired and exported to all of the world, including the Muslim world, in various means and channels. The danger is two-dimensional generated by secularization on the one hand, and bribes pascamodenisme value which is also the last issue of secularism itself is spread widely through the process of globalization. To restore this condition, the passage must necessarily be given to the creed to play a memorable role as an identity forming and the identity in society. In addition, the process also needs to be given in solid support without split by major institution in society, especially in family institution, educational institution-formal and informal–social growth, empire and the mass media.